Petrogenesis of the augen gneisses from Mahesh Khola section, Central Nepal - Regmi, Kamal Raj (Bulletin of the Department of Geology, 2008)
In Mahesh Khola section, Central Nepal the augen gneisses are exposed within the rocks of the Kulikhani Formation of the Bhimphedi Group, Kathmandu Complex. Major and trace element were analysed in this study. The gneisses show peraluminous Stype nature with high mol. A/CNK ratios. Mantle normalised trace element patterns have similar character with the Early Paleozoic S-type granite of the Lachlan Fold Belt of Australia and the Paleozoic granites of the Tso-Morari Crystalline Complex, Lakadh, India. Hence most probably the protoliths of these gneisses are the porphyritic S-type granite that intruded in the rocks of the Bhimphedi Group during Caledonian Orogeny. However the granite is sheared, deformed and metamorphosed. doi: 10.3126/bdg.v11i0.1429 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 13-22